Respuesta :
a = first number (larger number)
b = second number (smaller number)
a = 8b
a - b = 70 *
* since a is the larger number and their difference is positive, we want a-b.
plug the first equation into the second to get :
a - b = 70
(8b) - b = 70
8b - b = 70
Your correct answer would be choice #2.
b = second number (smaller number)
a = 8b
a - b = 70 *
* since a is the larger number and their difference is positive, we want a-b.
plug the first equation into the second to get :
a - b = 70
(8b) - b = 70
8b - b = 70
Your correct answer would be choice #2.